2003
DOI: 10.1103/physrevb.67.085111
|View full text |Cite
|
Sign up to set email alerts
|

Orbital state and magnetic properties ofLiV2O4

Abstract: LiV2O4 is one of the most puzzling compounds among transition metal oxides because of its heavy fermion like behavior at low temperatures. In this paper we present results for the orbital state and magnetic properties of LiV2O4 obtained from a combination of density functional theory within the local density approximation and dynamical mean-field theory (DMFT). The DMFT equations are solved by quantum Monte Carlo simulations. The trigonal crystal field splits the V 3d orbitals such that the a1g and e π g orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 78 publications
4
25
1
Order By: Relevance
“…Then, the hybridisation between those two subsets of electrons, as in f -electron materials, can give rise to heavy Fermion effects. Nekrasov et al (442) found a strong competition between antiferromagnetic direct (the exchange constant corresponds to an energy ≈-450 k B K) and ferromagnetic double exchange (≈ 1090 k B K). With these estimates it appears to be reasonable that these two contributions almost cancel so that the Kondo exchange (≈-630 k B K) prevails, resulting in heavy Fermion Kondo physics.…”
Section: 37mentioning
confidence: 99%
“…Then, the hybridisation between those two subsets of electrons, as in f -electron materials, can give rise to heavy Fermion effects. Nekrasov et al (442) found a strong competition between antiferromagnetic direct (the exchange constant corresponds to an energy ≈-450 k B K) and ferromagnetic double exchange (≈ 1090 k B K). With these estimates it appears to be reasonable that these two contributions almost cancel so that the Kondo exchange (≈-630 k B K) prevails, resulting in heavy Fermion Kondo physics.…”
Section: 37mentioning
confidence: 99%
“…In this respect LDA+DMFT, the recent merger [2][3][4][5][6] of LDA with the many-body dynamical mean-field theory (DMFT) [7][8][9][10], is a promising new approach which includes many-body aspects into realistic calculations. It has been successfully applied, in particular to calculate the total (k-integrated) spectra of transition-metal oxides like LaTiO 3 [2,11], [12][13][14], Sr(Ca)VO 3 [14][15][16][17][18][19][20], LiV 2 O 4 [21], Ca 2−x Sr x RuO 4 [22,23], CrO 2 [24], but also of Ni [25], Fe [25], and f -electron systems like Pu [26,27] and Ce [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the maximum entropy method [36], this technique allows us to calculate spectral functions [37,38,39,40].…”
Section: A Dynamical Mean-field Theorymentioning
confidence: 99%